17 Decannulation Following Tracheostomy in Children: A Systematic Review. (29th October 2021) - Verma, Rahul; Mocanu, Cora; Shi, Jenny; Miller, Michael; Chiang, Jackie; Wolter, Nikolaus; St-Laurent, Aaron; Amin, Reshma
Abstract: Primary Subject area: Respirology Background: Despite the large morbidity and potential mortality associated with tracheostomy tube decannulation failure, there are currently no consensus guidelines on pediatric tracheostomy decannulation. This has led to wide practice variation that is largely based on expert option. This is the largest review of pediatric decannulation protocols. Objectives: To systematically review the literature on existing pediatric decannulation protocols, including the role of polysomnography, and their clinical outcomes. Design/Methods: Five online databases were searched for relevant studies from database inception to May 29, 2020. Study inclusion was limited to publications that evaluated tracheostomy decannulation in children 18 years of age and younger. Independent reviewers extracted data, including patient demographics and primary indication for tracheostomy. Methods used to assess readiness for decannulation were noted, including the use of bronchoscopy, tracheostomy tube modifications, and gas exchange measurements. After decannulation, details regarding mode of ventilation, location and length of observation period, and clinical outcomes were also collected. Quality assessment of included studies was performed using the Newcastle-Ottawa Scale (NOS) tool. Descriptive statistical analyses were performed. Results: Twenty-three studies with 1328 children were included (Figure 1). Tracheostomy indications included upper airway obstruction at a well-defined anatomic site (37%), upper airway obstruction not at a well-defined site (13%), and need for long-term ventilation (50%). Bronchoscopy was routinely used in 96% of protocols. Tracheostomy tube modifications in the protocols included capping (83%), downsizing (57%), and fenestrations (9%). Measurements of gas exchange in the protocols included polysomnography (72%), oximetry (61%), blood gases (17%), and capnography with end-tidal CO2 (17%). After tracheostomy decannulation, children in 92% of protocols were transitioned to room air, and 38% of protocols used non-invasive ventilation. Most children (76%) were observed in hospital for 48 hours or less. Of all decannulation attempts, 79% were successful. Overall risk of bias in included studies was low. Conclusion: The absence of clear evidence-based guidelines in pediatric tracheostomy decannulation has led to large variability in clinical practice. Most protocols include bronchoscopy, tube modifications, gas exchange measurements, and brief hospital admission. Polysomnography plays an integral role in assessing the majority of children for tracheostomy removal. Evidence-based guidelines to standardize pediatric tracheostomy care remain an urgent priority.